Can sport-specific training affect vertical jumping ability during puberty? - Konstantina Karatrantou; Vassilis Gerodimos; Vasileios Voutselas; Nikolaos Manouras; Konstantinos Famisis; Panagiotis Ioakimidis (Termedia Publishing House, 2019)
Vertical jumping ability (VJ) is an important component for successful performance in various team sports such as volleyball, basketball, and soccer. There is evidence that the sport-specific training in these sports may affect the development of VJ throughout the developmental years. Thus, the main objective of this study was to investigate the sport-related effect (volleyball, basketball, soccer) on vertical jumping ability (VJ) and on the stretch-shortening cycle (SSC) during puberty. 320 boys (12-15 years old) - 80 basketball players (BP), 80 soccer players (SP), 80 volleyball players (VP) and 80 non-athletes (NA) - participated in the present study. VJ was evaluated by the squat jump (SJ) and countermovement jump (CMJ) tests, and the contribution of SSC was calculated. The SJ and CMJ were significantly higher in VP vs. NA at the age of 12 years old and significantly greater in all sports vs. NA at the age of 13, 14 and 15 years. Furthermore, 15-year-old VP demonstrated significantly higher SJ and CMJ compared with BP and SP (p 0.05). Finally, pairwise comparisons revealed non-significant sport- and agerelated differences (p > .05) in SSC. The pattern of age-related increase in VJ is different between athletes and non-athletes during puberty. Furthermore, sport-specific training adaptations are evident at the age of 15 years old where VP demonstrate greater VJ than BP and SP, while in younger age groups, there are no significant differences in VJ between athletes of different sports.